Anthocyanin Identification in Miana Leaf (Coleus scutellarioides L. Benth) Extracts Using Different Solvents and Maceration Times for Application as a Poultry Feed Additive - Jannah, Miftahul; Harahap, Armita; Sardi, Valdy Filando; Rizal, Yose; Ismed, Friardi; Mahata, Maria Endo (Trends in Sciences, 2026)
This study aims to identify the type of solvents and their maceration durations for the extraction of anthocyanins from Coleus scutellarioides L. Benth (C. scutellarioides) leaves using the maceration method. It also aims to characterize the anthocyanin profile, which could be utilized as a potential feed additive to reduce cholesterol levels in poultry meat. The study employed a completely randomized design with 2 factors. The first factor (A) was solvent: Aquadest, aquadest + 0.5% citric acid, and 70% ethanol. The second factor (B) was maceration durations: 6, 12, 24, and 48 h for C. scutellarioides leaves. Measured variables included color measurement, extract yield, total anthocyanin content (TAC), thin layer chromatography (TLC) extract-yield profile, and identification of anthocyanins by LC-MS/MS. Statistical analysis showed a significant interaction effect (p < 0.05) between solvent type and maceration duration on color measurement, extract yield, and TAC of C. scutellarioides extract. The TLC profile of C. scutellarioides extract using the citroborate reagent revealed 7 distinct spots with aquadest, 8 with aquadest with 0.5% citric acid, and 8 with 70% ethanol as solvents. Based on the highest TAC value obtained for each solvent type and maceration duration, LC-MS/MS analysis was conducted. The results identified 4 different anthocyanin compounds in the aquadest extract, 6 in the aquadest with 0.5% citric acid extract, and 5 in the 70% ethanol extract. It can be concluded that the optimal solvent type and maceration duration for anthocyanin extraction from C. scutellarioides are aquadest with 0.5% citric acid for 12 h. Under these conditions, 6 distinct anthocyanins were identified: cyanidin-3-glucoside, cyanidin 3-O-(p-coumaroyl) glucoside-5-O-malonyglucoside I, cyanidin-3-O-glucuronide, pelargonidin-3-glucuronide, cyanidin, and pelargonidin, with a total phenolic content of 72.14 mg GAE/g extract. Three of these (cyanidin-3-glucoside, cyanidin, and pelargonidin) have been reported to inhibit cholesterol synthesis. HIGHLIGHTS This study optimized anthocyanin extraction from Coleus scutellarioides Benth leaves by varying solvents and maceration durations. A significant interaction (p < 0.05) between solvent type and maceration duration affected color parameters, extract yield, and total anthocyanin content (TAC). The combination of distilled water with 0.5% citric acid for 12 h produced the highest anthocyanin concentration (292.95 mg/L), with 6 types of anthocyanins identified. Six anthocyanin were identified in the extract obtained using distilled water with 0.5% citric acid through LC-MS/MS analysis: Cyanidin-3-glucoside, pelargonidin-3-glucuronide, and cyanidin 3-O-(p-coumaroyl) glucoside-5-O-malonylglucoside I. The compounds cyanidin-3-glucoside, cyanidin, and pelargonidin have each been associated with inhibition of HMG-CoA reductase. This association suggests that these specific compounds may serve as natural anti-cholesterol feed additives for poultry. GRAPHICAL ABSTRACT